2014
DOI: 10.1038/jp.2014.186
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin use for neuroprotection in perinatal asphyxia: a randomized controlled pilot study

Abstract: Early administration of melatonin to asphyxiated term neonates is feasible and may ameliorate brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(140 citation statements)
references
References 40 publications
7
131
0
2
Order By: Relevance
“…They reported that melatonin augmented a hypothermia-improved cerebral energy metabolism and reduced cell death after perinatal asphyxia, with plasma concentrations of melatonin ranging between 17 and 31 mg/mL (74-134 μM). In agreement, a small randomized controlled pilot study in which melatonin was enterally administered to neonates with HIE undergoing hypothermia showed fewer seizures on follow-up EEG and less white matter abnormalities in the melatonin/hypothermia group [27]. At 6 months, this study also reported improved survival without neurological or developmental abnormalities [27].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…They reported that melatonin augmented a hypothermia-improved cerebral energy metabolism and reduced cell death after perinatal asphyxia, with plasma concentrations of melatonin ranging between 17 and 31 mg/mL (74-134 μM). In agreement, a small randomized controlled pilot study in which melatonin was enterally administered to neonates with HIE undergoing hypothermia showed fewer seizures on follow-up EEG and less white matter abnormalities in the melatonin/hypothermia group [27]. At 6 months, this study also reported improved survival without neurological or developmental abnormalities [27].…”
Section: Discussionsupporting
confidence: 67%
“…In agreement, a small randomized controlled pilot study in which melatonin was enterally administered to neonates with HIE undergoing hypothermia showed fewer seizures on follow-up EEG and less white matter abnormalities in the melatonin/hypothermia group [27]. At 6 months, this study also reported improved survival without neurological or developmental abnormalities [27]. A clinical trial to study the neuroprotective properties and the appropriate dosage of melatonin for neonates undergoing therapeutic hypothermia after HIE is currently in progress [28].…”
Section: Discussionmentioning
confidence: 49%
“…Due to its significant biological effect in the regulation of sleep-wake cycle, exogenous MEL is widely used in clinic for the treatment of sleep-related disorders. In recent years, the use of exogenous MEL has been enlarged with the identification of its other potential bioactivities in neuroprotection [3], immunoregulation [4], antioxidation [5,6], anti-tumor [7], and cardioprotection [8].…”
Section: Introductionmentioning
confidence: 99%
“…На моделях асфик-сии у животных мелатонин показал способность защи-тить мозг как самостоятельно, так в комбинации с гипо-термией [108,109]. Появились и первые клинические данные: рандомизированное контролируемое пилотное исследование в Египте с участием 30 новорожденных с ГИП и 15 здоровых детей показало, что сочетание внутривенного введения мелатонина (в течение первых 5 дней) и терапевтической гипотермии у детей с уме-ренной и тяжелой степенью ГИП было эффективным в снижении окислительного стресса, улучшало состояние белого вещества по данным МРТ, уменьшало судорожную готовность на ЭЭГ и, в конечном счете, приводило к улуч-шению выживаемости с благоприятным исходом в пси-хомоторном развитии в возрасте 6 мес [110]. Показана также эффективность мелатонина для недоношенных детей [111].…”
Section: педиатрическая фармакологияunclassified